On The Psychic Constitution of a Nation - Smirnovas, Anatolijus (Problemos, 1972)
The paper provides an analysis of some methodological problems arising in the study of the psychic constitution of a nation. The author suggests that the psychic constitution of a nation is not a totality of national peculiarities only but something common to all nations. In bourgeois nations their psychic constitution presents a unity of contradicting forms of its manifestations. The psychic constitution of socialist nations is free of such contradictions and is indivisible for the whole of the nation. Despite adaptation and relative stability, the psychic constitution of a nation undergoes changes. The most profound ones occur when the socialist nation is being formed. Socialism creates favourable conditions for psychic constitution rapprochement of socialist nations. This process is part of an all-round rapprochement of socialist nations in the course of building communism in our country.